VERIFICATION VERIFIKASI METODE ANALISIS ZAT AKTIF ZIRAM MENGGUNAKAN TITRASI IODIMETRI: VERIFICATION OF ZIRAM ACTIVE ANALYSIS METHOD USING IODIMETRY TITRATION - renny_futeri, Renny Futeri; Armin, M.Ikhlas; Rika Putri, Gustiarini; Dewati Samah, Selfa Dewati Samah (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
is a fungicide in agriculture that is used for various types of fungi and plant diseases, mainly applied to plant foliage, and is also used as a soil or seed treatment. For this reason, it is necessary to confirm the composition or active substance in the fungicide sample so that it can work as intended. To ascertain the composition of the active substance, a test concentration analysis method is required, namely iodimetry titration. Before a method is used as a standard method, it is necessary to verify the method so that this method provides precise and thorough results. The verification process involves several parameters, namely precision, accuracy and linearity with the acceptance requirements for each parameter being % RSD < 2 % for precision, % recovery in the range of 98-102 % and determination > 0.9970 for linearity. From the tests that have been carried out, it was found that the precision parameters had a % RSD of 0.017320%, the accuracy parameters had a %recovery of 99.80% and the linearity parameters had a coefficient of determination (r2) of 0.027. The results of research on samples showed that Ziram 96% TC levels varied between 95-95.03%. This range is within the permitted content limits based on the CoA (Certificate of Analysis), namely 95-95.2%.